Diagnostic accuracy of a bovine specific electronic beta-hydroxybutyrate handheld meter in fresh blood and stored serum samples. (March 2021) - Rodriguez, Z.; Caixeta, L.S.; Cramer, G.
Highlights: The nova vet handheld beta-hydroxybutyrate meter showed high accuracy and precision. Anticoagulants caused minimal interference in measurements. The best calibration factor on cattle was obtained with the default slope setting. Abstract: This study aims to evaluate the diagnostic accuracy of the bovine specific beta-hydroxybutyrate (BHB ) meter Nova Vet (NVET ). We evaluated the accuracy and agreement of the NVET in fresh blood and thawed serum with the reference laboratory assay; and the repeatability, the interference by anticoagulants, and the optimum slope calibration factor. Individual blood samples were collected from 200 Holstein and crossbred cows between 3 and 14 days post-calving from 13 dairy herds in Minnesota. Using a laboratory assay with a cut point of 1.2 BHB mmol/L hyperketonemia prevalence was 10.6% (95% CI: 6.7, 15.8). The sensitivity of NVET in blood and serum was 100.0% while the specificity was 98.3 and 97.7% respectively. The agreement between NVET and the laboratory assay was the highest using blood samples (concordance correlation coefficient –CCC = 96.2, 95% CI: 95.0, 97.1. The coefficient of variation including within day (intra-meter), between- days, and -batches was 13.4% when testing blood samples. Minimal interference was observed with the use of anticoagulants (K-EDTA and Li-Heparin, CCC 0.90 and 0.93 respectively) in reference to whole blood without anticoagulant. The best calibration slope factor in serum was 1.0 (Youden's index: 0.98). Results suggest that the NVET device maintained a high accuracy and precision to quantified BHB concentration when applied in fresh blood and thawed serum under field conditions using the default calibration slope (1.0), and with minimal anticoagulant interference when used in whole blood samples. Graphical abstract: Image, graphical abstract